1989
DOI: 10.2331/suisan.55.91
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of feedstuffs by the marine shrimp Penaeus vannamei BOONE.

Abstract: The apparent dry matter digestibility (ADMD), apparent protein digestibility (APD), and apparent amino acid digestibility (AAAD) of thirteen feedstuffs used for marine shrimp diets were determined for the marine shrimp, Penaeus vannamei. The feedstuffs evaluated were casein, corn starch, gelatin, soy protein, wheat gluten, fish meal, rice bran, shrimp meal, soybean meal, squid meal, cellulose, chitin, and diatomaceous sand. Each feedstuff comprised 88% of the experimental diets. The ADMD values ranged from 91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
113
2
8

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 3 publications
25
113
2
8
Order By: Relevance
“…Similar results have been reported for untreated GRM in P. monodon (Rajamohammed, 2012) and the findings of Akiyama et al (1989) suggested that it can be attributed to better assimilation of crude protein. Fungal fermentation has significantly (p<0.05) increased dry matter digestibility et al, 2016).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results have been reported for untreated GRM in P. monodon (Rajamohammed, 2012) and the findings of Akiyama et al (1989) suggested that it can be attributed to better assimilation of crude protein. Fungal fermentation has significantly (p<0.05) increased dry matter digestibility et al, 2016).…”
Section: Resultssupporting
confidence: 79%
“…Shi et al (2015) reported that A. niger produced >800 U g -1 of protease during the fermentation of rapeseed meal. Among amino acids, both untreated and fermented ingredients have shown a poor digestibility for alanine and glycine (Table 4) and the findings of Akiyama et al (1989) suggested that it can be due to the secretion of chitinous peritropic membrane which surrounds the faeces. The same was in agreement with the findings of Dayal et al (2011) for sunflower oil cake (SFC) in the diet of P. monodon, who also reported that chitin had a higher content of alanine and glycine than other amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…SHF presented a CDADM of 77.78%, which is lower than that found by Terrazas-Fierro et al (2010) (84.0%), but higher than that found by Akiyama et al (1989) (56.8%). Such differences have relationship with ingredient quality and processing methods, which have varying times and temperatures of preparation.…”
Section: Resultscontrasting
confidence: 63%
“…Unfortunately, despite three decades of numerous replacement research, fish meal remains the prime protein ingredient in the majority of commercial fish feeds. Among plant protein, soybean meal is the extensively used ingredient in aquaculture diets due to its wide availability, comparatively low market price and promising nutrient profile (Akiyama et al 1989;Gatlin et al 2007;Trosvik et al 2012;Cummins et al 2013;Cummins et al 2017). However, the price of soybean Values are average from duplicate groups of samples a Diets represent; control (without black soldier fly larval meal inclusion), BSFL25 (25%), BSFL50 (50%), BSFL75 (75%) and BSFL100 (100% fish meal replacement using black soldier fly larval meal) meal and other plant feedstuff has also increased dramatically due to their growing demand for the direct human consumption (FAO 2009).…”
Section: Discussionmentioning
confidence: 99%